COMPARATIVE STUDY ON MILK COMPOSITION AND SOMATIC CELL COUNT BETWEEN HEALTHY KOSALI AND THARPARKAR BREED OF CATTLE - Subrat Kumar Dash; Piyusha Bhainsare (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Kosali is a new cattle breed of Chhattisgarh planes in which composition of the milk remain unestablished till now. The present study established the milk composition and somatic cell count  in healthy Kosali cow in comparison with Tharparkar breed.  Fifteen animals, each from Kosali and Tharparkar cows at early lactational stage were used to study milk composition. The percentage of fat, protein, total solid and solid not fat in the milk of Kosali breed was significantly lowered than Tharparkar. Lactose percentage in the milk of both Kosali and Tharparkar cow was comparable. Milk enzymes viz. lactate dehydrogenase, alkaline phosphatase, aspartate aminotransferase and average milk somatic cell count differed  non-significantly between healthy  Kosali and Tharparkar. The current study established the nutritional and enzymatic composition of the milk of Kosali breed in relation to Tharparkar .